Zwitterionic molecule layer for inhibiting microbial corrosion of copper alloy. Issue 1 (2nd January 2018) - Xu, Fengling; Qiu, Zhenghui; Qiu, Ri; Yang, Jiadong; Lin, Cunguo
Abstract : Purpose: For mitigating biocorrosion induced by sulfate-reducing bacteria (SRB) in seawater, the zwitterionic molecule layer (ZML) of poly (sulfobetaine methacrylate) is grafted onto B10 surface by chemical vapor deposition and surface-initiated atom transfer radical polymerization. Design/methodology/approach: Energy-dispersive spectroscopy-attenuated total reflectance Fourier transform infrared spectroscopy and static contact angle measurements are used to characterize the as-formed layer. Findings: After surface modification, B10 can significantly reduce SRB adhesion, demonstrating the good antifouling property. Further, the biocorrosion inhibition is investigated by potentiodynamic polarization and electrochemical impedance spectroscopy, indicating that ZML exhibits high resistance to biocorrosion with inhibition efficiency of approximately 90 per cent. Originality/value: ZML performs a dual feature, i.e. antifouling film and corrosion inhibitor, for the biocorrosion inhibition.